Potret kehidupan ekonomi pekerja wanita pada pabrik rokok dalam kajian gender - Mahyaya Fuaida (Universitas Negeri Malang, 2018)
In the current era most women play a role in building the family economy. Women help husbands to earn income to sustain family economic life. Not only take care of households, women are also good at working outdoors. Even today many women prefer a career and put aside the household affairs. But in Indonesia there are still many women who are discriminated against in terms of employment, women are made up of second-class citizens and placed in the lowest job positions. The cigarette factory is a factory where most of its employees are women. Most of the women who work in cigarette factories make the job as the main livelihood in the family. Female workers in cigarette factories are placed in production for grinding and packing, the part being the lowest in the job classification in cigarette factories. In this context gender equality means that all human beings are free to develop their personal abilities and choose without being constrained by stereotypes and prejudices about gender roles or characteristics of men and women. Women also have the right to get a good livelihood. Gender equality does not mean that men and women are equal, or have become the same, but rights, responsibilities, social status and access to resources are independent of gender. Through this research, researchers want to reveal in more depth how the life of female workers in cigarette factory. This study used a qualitative approach to the type of phenomenal research, by interviewing several female workers selected through snowball techniques. This research is located in Sorgum cigarette factory of Malang regency. The results showed that female workers at the Sorgum Malang cigarette factory have not reached a good economy despite working for decades.DOI: 10.17977/um022v3i12018p048